Nowcasting for Africa: advances, potential and value. (23rd March 2021) - Roberts, Alexander J.; Fletcher, Jennifer K.; Groves, James; Marsham, John H.; Parker, Douglas J.; Blyth, Alan M.; Adefisan, Elijah A.; Ajayi, Vincent O.; Barrette, Ronald; de Coning, Estelle; Dione, Cheikh; Diop, Abdoulahat; et al.
Abstract : There is a great demand to improve predictions of high‐impact weather across the African continent. This is because of the high frequency of intense convective storms that often produce severe flooding, strong winds and lightning, combined with the vulnerability of people, infrastructure and businesses to such hazards. The skill of numerical weather prediction over Africa is still low, even for lead times of less than 24 hours. Therefore, there is a particular need to deliver nowcasting of events as they occur. However, there remains a widespread lack of provision of nowcasting across Africa and virtually no use of automated nowcasting systems or tools. This limits the ability of national meteorological services to issue warnings and therefore potentially prevent the loss of life and significant financial losses. Coverage by meteorological radars is still very limited, but geostationary satellites provide regular high resolution data of the often large and long‐lived storms. As such, there is an opportunity to improve satellite‐based nowcasting capability in Africa. Work being undertaken as part of the Global Challenges Research Fund African SWIFT (Science for Weather Information and Forecasting Techniques) project is starting to improve the nowcasting of African convective systems and so the ability to provide timely warnings of extreme weather providing a wide range of benefits. Abstract : The high frequency of intense convective storms means there is a great demand to improve predictions of high‐impact weather across Africa. The low skill of numerical weather prediction over Africa, even for short lead times highlights the need to deliver nowcasting based on satellite data. The Global Challenges Research Fund African SWIFT (Science for Weather Information and Forecasting Techniques) project is working to improve the nowcasting of African convective systems and so the ability to provide timely warnings.